2017
DOI: 10.5742/mewfm.2017.93136
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cognitive - Existential Group Therapy on Reducing Demoralization in the Elderly

Abstract: Introduction and Objective: Elderly people face existential issues such as death, loss of meaning in life, fear of death, lack of life and last chances. If people, cannot effectively confront it, this loss of meaning in life, will form the main core of a set of syndromes that are called "demoralization". This study aims to investigate the effectiveness of cognitive-existential therapy on reducing demoralization in the elderly. Method: The present study was carried out using a pretest-posttest semi-experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Investigations into mental health issues affecting this population have revealed that mental health is a major concern among the elderly. During this stage of life, common complaints among the elderly include feelings of loneliness, fatigue, boredom, unimportance, and insomnia (6)(7)(8). Loneliness, rejection from family members, depression, and insecurity are all negative mental consequences of living in a nursing home (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into mental health issues affecting this population have revealed that mental health is a major concern among the elderly. During this stage of life, common complaints among the elderly include feelings of loneliness, fatigue, boredom, unimportance, and insomnia (6)(7)(8). Loneliness, rejection from family members, depression, and insecurity are all negative mental consequences of living in a nursing home (9,10).…”
Section: Introductionmentioning
confidence: 99%